A unifying computational approach for the lower-bound limit analysis of systems of masonry arches and buttresses. (15th October 2020) - Nodargi, Nicola A.; Bisegna, Paolo
Highlights: The lower-bound limit analysis of systems of arches and buttresses is addressed. The monodimensional masonry element with multiple potential failure sections is defined. The resulting linear programming problem is solved at negligible computational cost. Collapse mechanisms due to linear cracks of unknown position/orientation are detected. The proposed approach exhibits excellent performances for real structures. Abstract: The lower-bound limit analysis of arbitrary systems of masonry arches and buttresses is addressed. Main motivation is the observation that, not only the position, but also the orientation of the failure sections in an arch or a buttress might not be known in advance in practical applications. To overcome the limitations stemming from the classical notion of element with prescribed stereotomy, the original model of monodimensional masonry structural element with multiple potential failure sections with different orientations is introduced. Accordingly, the lower-bound limit analysis problem for systems of masonry arches and buttresses is formulated as a straightforward linear programming problem. The predicting capabilities of the proposed approach are investigated in numerical simulations, proving that an accurate and safe prediction of the loading capacity of real structures can be derived in a completely automatic fashion.